2020
DOI: 10.3390/ijerph17124260
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia is Associated with Inflammation, Bone Resorption, Vitamin B12 and Folate Deficiency and MTHFR C677T Polymorphism in Postmenopausal Women with Decreased Bone Mineral Density

Abstract: Osteoporosis is an age-related bone disease, affecting mainly postmenopausal women, characterized by decreased bone mineral density (BMD) and consequent risk of fractures. Homocysteine (Hcy), a sulfur-aminoacid whose serum level is regulated by methylenetrahydrofolate reductase (MTHFR) activity and vitamin B12 and folate as cofactors, is a risk factor for inflammatory diseases. Literature data concerning the link between Hcy and osteoporosis are still debated. The aim of our study was to assess the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 56 publications
0
27
0
1
Order By: Relevance
“…Osteoporosis is also a predominantly female pathology: among diseases afflicting women more than men, osteoporosis is at the first place [ 10 11 ]. In addition to aging and menopausa, other conditions, such as underlying diseases and/or the use of drugs impacting the bone, can also cause “secondary” osteoporosis [ 12 13 ]. Five per cent of people aged 50 and 50% at age 85 have decreased BMD, whereas more than 75% of women over 60 are affected.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is also a predominantly female pathology: among diseases afflicting women more than men, osteoporosis is at the first place [ 10 11 ]. In addition to aging and menopausa, other conditions, such as underlying diseases and/or the use of drugs impacting the bone, can also cause “secondary” osteoporosis [ 12 13 ]. Five per cent of people aged 50 and 50% at age 85 have decreased BMD, whereas more than 75% of women over 60 are affected.…”
Section: Introductionmentioning
confidence: 99%
“…An altered gut microbiome can reduce folic acid absorption in the jejunum, leading to hyperhomocysteinemia, which, in turn, induces extracellular bone matrix degradation and decreases the bone mineral density [ 40 ]. Gut bacteria also affect the brain–gut axis by regulating the neurotransmitter serotonin (5-HT) [ 41 ]. Gut-derived 5-HT decreases bone formation, while brain-derived 5-HT has the opposite effect of increasing bone formation [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that active oxygen is involved in regulating the formation and activity of osteoblasts and osteoclasts and is involved in the occurrence and development of osteoporosis [10]. In addition, inflammatory cytokines and homocysteine are playing important roles in the development of DOP, they can increase osteoclastogenesis, leading to increased bone resorption and osteoporosis [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%